Sagot :
a+b(c+d) = a + bc + bd
a (b+c)(d+e) = (ab + ac)(d+e)
= abd + abe + acd + ace
( a+b)(c+d)(e+f) = (ac + ad + bc + bd)(e + f)
= ace + acf + ade + adf + bce + bcf + bde + bdf
( a+b)(c+d)-(e+f)(g+h)= ac + ad + bc + bd - eg - eh - fg - fh
( a+b)(c+d)+(e+f)(g+h)= ac + ad + bc + bd + eg + eh + fg + fh
voilà :)
a x c + a x d + b x c + b x d
a x b + a x c + a x d + a x e
a x c + a x d + b x c + b x d - ( e x g + e x h + f x g + f x h ).
Pour la dernière c'est pareil sauf qu'à la place du - c'est un + .
a x b + a x c + a x d + a x e
a x c + a x d + b x c + b x d - ( e x g + e x h + f x g + f x h ).
Pour la dernière c'est pareil sauf qu'à la place du - c'est un + .